(3ebGeGJ GdHcQj GdUOjbjs - (3GdHcQj , eMeO Hf eMeO CHj GdMSf Hf eMeO Hf YHO GdQMef, TeS GdOjf CHh GdecGQe,J (B994 (3g` s ((3SdGeI s)
(3ChdgG (B:s
(3hHYO, ajbhd abjQ dH edC TLfj cfJ cKjQkG eG CSeY HPcQ Gdjef hQLGdgG ef cd MSf s
(3BNQgG (B:s
(3hGdYRe GdYhO Edi bQjI GdeTHg LfGJ GdfYje, EPG hbY GdEPf ef GdYdje s
(3HgG fXGe GdJYbjHIs
(3hGdfSNI ebGHdIs
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B60 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B11 - (3U (B281s
Keywords: (3GdCOHs